Understanding China’s Engagements in South Asia: Is It Assertive Wolf Warrior, A Cooperative Traditional Or A Crucible of Conglomerate? (Journal of Asian Development Studies, 2024)
China’s engagements in South Asia have various dynamics. This study seeks to explore these dynamics by integrating theoretical perspectives from both Soft Power and Power Transition Theory, examining how China's diplomatic investments, military and diplomatic postures align with these theories. Within the conceptualization of Chinese engagement in the region and to assess the kind of approach China utilizes, the paper will analyze specific case studies of China’s interactions with India, Pakistan, and other smaller South Asian states, which will provide a bigger picture of these approach/engagements that reflects traditional diplomacy or the more assertive Wolf Warrior approach. In terms of methodology, this research adopts an ‘eye of the beholder’ and qualitative approach, utilizing case studies, primary sources and secondary sources in scientific manner to examine the rhetoric and actions of China.